2018
DOI: 10.4314/jfas.v8i3.3
|View full text |Cite
|
Sign up to set email alerts
|

Rich extract on total polyphenols and antioxidant activity obtained by conventional and non-conventional methods from Ahmeur Bouamer grape seed

Abstract: Conventional and non-conventional extraction methods were applied in the first time for the determination of total polyphenols from Ahmeur Bouamer, an anthoctonous variety grape seeds. Independently of the time and temperature, a positive effect of particle size parameter on maceration has been noted and relativly high concentrations in polyphenols for 500 μm (67.78 ± 0.46 mg GAE/gdm), 500-355 μm (90.95 ± 0.24 mg GAE/gdm) and 355-180 µm (114.82 ± 1.24 mg GAE/gdm) have been obtained. The higher value of yield w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 23 publications
1
3
0
Order By: Relevance
“…The DPPH and ABTS scavenging assays resulted in close values obtained through the two methods for the same organ and the same solvent but those obtained by DPPH method were slightly highest indicating a lower inhibition capacity compared to ABTS. Our observations are in line with those indicated by some authors which report that ABTS inhibition for samples from vegetables, fruits and beverages is higher than DPPH inhibition (Ghouila et al, 2016;Floegel et al, 2011). This is explained by the fact that the DPPH method is characterized by a lower sensitivity.…”
Section: Comparison Between Dpph and Abts Methodssupporting
confidence: 93%
“…The DPPH and ABTS scavenging assays resulted in close values obtained through the two methods for the same organ and the same solvent but those obtained by DPPH method were slightly highest indicating a lower inhibition capacity compared to ABTS. Our observations are in line with those indicated by some authors which report that ABTS inhibition for samples from vegetables, fruits and beverages is higher than DPPH inhibition (Ghouila et al, 2016;Floegel et al, 2011). This is explained by the fact that the DPPH method is characterized by a lower sensitivity.…”
Section: Comparison Between Dpph and Abts Methodssupporting
confidence: 93%
“…The other important factor for effective extraction of grape seeds is the type of technique used. A number of publications have described the application of both conventional and non-conventional extraction methods [22,23]. In the present study, experiments were carried out to extract antioxidants from Pinot Noir red grape seeds using two conventional techniques -a shaker and a magnetic stirrer.…”
Section: Resultsmentioning
confidence: 99%
“…The results obtained show that GSE is a strong ABTS +• radical cation inhibitor -2203.50 µM TE/g DW (551.515 mg TE/g DW). Guaita and Bosso [26] obtained lower ABTS results for seed extracts of different red grape species 109 -185 mg TE/g DW, but Ghouila et al [23] obtained higher 3902 µM TE/g DW. Li et al [24] received lower antioxidant capacity of seed extract from Cabernet Sauvignon -673.5 µM TE/g.…”
Section: Yeld Tpcmentioning
confidence: 93%
“…The ABTS results ( Table 2 ) are similar to the results of other studies and show that GSEs are strong ABTS + radical cation inhibitors (1907.24–2273.90 µM TE/g DW). Guaita and Bosso (2019) [ 22 ] reported lower ABTS values for seed extracts of different red grape species—109–185 mg/g DW (or 434.91–738.15 µM TE/g DW) but Ghouila et al (2016) [ 48 ] showed higher values—3902 µM TE/g DW. Selkur et al (2011) [ 47 ] reported an antioxidant capacity determined by ABTS of 16.45 µM TE/g.…”
Section: Discussionmentioning
confidence: 99%